PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR & SHARE PADA MATA PELAJARAN PKN DI SMA NEGERI 1 TOMPASO - Theodorus Pangalila; Mardan Umar; Andro Waney (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2022)
The work of the study is to identify if the model cooperative learning type thinks pair share can increase the result of students study in science at the senior high school 1 in Tompasol. The result of the study is a quantitative study with a type of experimental research. The subject in this study is the whole XI IPS 1 as an experiment class and XI IPS 2 as a control class. The results of the study conducted showed that class XI, which is taught using the cooperative learning type think pair share obtains an average of 93.35 and a standard deviation of 3.730, and the XI classes taught by the conventional learning model gained an average of 76.27 and standard deviation 2.475. Further from the results of the hypothetical test performed show that    or 17.077 2.056 at 5% trust. Thus it may be concluded that the model cooperative learning type thinks pair share are better applied to the process of learning than the conventional learning model, as it has a positive and significant impact on student learning at senior high school 1 in Tompaso.